Sexual dimorphism in the fetal cardiac response to maternal nutrient restriction. (July 2017) - Muralimanoharan, Sribalasubashini; Li, Cun; Nakayasu, Ernesto S.; Casey, Cameron P.; Metz, Thomas O.; Nathanielsz, Peter W.; Maloyan, Alina
Abstract: Poor maternal nutrition causes intrauterine growth restriction (IUGR); however, its effects on fetal cardiac development are unclear. We have developed a baboon model of moderate maternal undernutrition, leading to IUGR. We hypothesized that the IUGR affects fetal cardiac structure and metabolism. Six control pregnant baboons ate ad-libitum (CTRL)) or 70% CTRL from 0.16 of gestation (G). Fetuses were euthanized at C-section at 0.9G under general anesthesia. Male but not female IUGR fetuses showed left ventricular fibrosis inversely correlated with birth weight. Expression of extracellular matrix protein TSP-1 was increased (p < 0.05) in male IUGR. Expression of cardiac fibrotic markers TGFβ, SMAD3 and ALK-1 were downregulated in male IUGRs with no difference in females. Autophagy was present in male IUGR evidenced by upregulation of ATG7 expression and lipidation LC3B. Global miRNA expression profiling revealed 56 annotated and novel cardiac miRNAs exclusively dysregulated in female IUGR, and 38 cardiac miRNAs were exclusively dysregulated in males (p < 0.05). Fifteen (CTRL) and 23 (IUGR) miRNAs, were differentially expressed between males and females (p < 0.05) suggesting sexual dimorphism, which can be at least partially explained by differential expression of upstream transcription factors (e.g. HNF4α, and NFκB p50). Lipidomics analysis of fetal cardiac tissue exhibited a net increase in diacylglycerol and plasmalogens and a decrease in triglycerides and phosphatidylcholines. In summary, IUGR resulting from decreased maternal nutrition is associated with sex-dependent dysregulations in cardiac structure, miRNA expression, and lipid metabolism. If these changes persist postnatally, they may program offspring for higher later life cardiac risk. Highlights: Maternal undernutrition causes cardiac fibrosis and activates cardiac autophagy in a sex-dependent manner. The expression of fetal cardiac miRNA is dysregulated by maternal undernutrition in a sex-dependent manner. Maternal undernutrition affects fetal cardiac lipid profile.